Two variants of uterine leiomyoma in Malaysia's last Sumatran rhinoceros (Dicerorhinus sumatrensis) - Salleh, Annas; Zainuddin, Zainal Zahari; Mohamed Tarmizi, Mohamed Reza; Yap, Keng Chee; Saad, Mohd Zamri (Taylor & Francis, 2020)
Following its capture in March 2014, an adult female Sumatran rhinoceros frequently showed profuse vaginal bleeding. An ultrasonography suggested the presence of multiple reproductive lesions, including two uterine masses which were suspected to be leiomyomas. Soon after, an open pyometra was confirmed. Later in November 2019, the patient died and necropsy confirmed the presence of two uterine masses; one was located at the cervico-uterine junction and another in the uterine body, with pyometra, and cystic endometrial hyerplasia. Based on histological, special stains, and immunohistochemical examination, it was shown that one of the masses was composed of large, ovoid and polyhedral neoplastic mesenchymal cells with eosinophilic cytoplasm and a few binucleated cells surrounded by collagen fibres. It was tested positive for SMA and vimentin, while negative for desmin, cytokeratin AE1/AE3, EMA, CD34, and S100. The other mass was composed of mesenchymal cells undergoing myxoid degeneration as evidenced by the presence of glycosaminoglycan-rich matrix. It was tested positive for SMA, vimentin, partially positive for desmin, and negative for the other markers. With the aid of human medical nomenclature, these masses were diagnosed as epithelioid leiomyoma and myxoid leiomyoma, respectively. This report provides a clinical presentation, and histologic descriptions of the two variants of leiomyomas that have not been reported in veterinary medicine.